Determinan Ketahanan Pangan di Indonesia (Pendekatan Integratif Berbasis Regresi dan Klasterisasi K-Means) - Maulia Siti Mukharohmah; Reni Eka Septiani; Nurul Fadhilah; Retno Rekayati (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2025)
Food security has become a central focus of government policy. However, 44% of Indonesia's provinces still record a Food Security Index below the national average. This study aims to identify the economic, agricultural, and social factors influencing food security and to classify provinces based on these characteristics through spatial visualization. The main scientific contribution of this study lies in integrating regression analysis, regional clustering, and spatial mapping to reveal interprovincial food security patterns in Indonesia, which remain underexplored in the existing literature. An integrative methodological approach was employed, combining multiple linear regression analysis, k-means clustering, and spatial analysis. Secondary data cover 34 Indonesian provinces in 2023 and are obtained from Statistics Indonesia and the National Food Agency, with analyses conducted using Stata 17 and ArcGIS 10.8. The empirical results indicate that poverty levels significantly and negatively affect the Food Security Index, while rice productivity and the social capital index exert positive influences. Spatially, provinces in Eastern Indonesia tend to exhibit the highest poverty levels, Java and Bali record the highest rice productivity, and the highest levels of social capital are concentrated in several provinces in Central and Eastern Indonesia. The study provides a scientific foundation for policy formulation on food security enhancement and offers a clear framework for establishing intervention priorities tailored to regional characteristics. These findings enhance the empirical understanding of the determinants and spatial patterns of food security in Indonesia, although this study does not incorporate climatic factors or market access as explanatory variables. The study provides a scientific foundation for policy formulation on food security enhancement and offers a clear framework for establishing intervention priorities tailored to regional characteristics.